Relative viscoelasticity of soy protein hydrolysate and polysaccharides mixtures at cooling conditions analyzed by response surface methodology - Martínez, Karina Dafne (2012)
The objective of this work was to study the relative viscoelasticity of soy protein hydrolysate and polysaccharides mixtures at cooling conditions analyzed by response surface methodology.Systems of soy protein hydrolysate (HSP) of 4% degree of hydrolysis, a hydroxypropylmethylcellulose (E4M) and kappa-carrageenan (κC) were made with concentrations conformed by Doehlert matrix as experimental design used.The samples were subjected to dynamic rheological studies with a control stress rheometer, Paar Physica MCR 300, with a program with a heating and a cooling period. At the end of the cooling at 10 °C the relative viscoelasticity (tan. δ) was evaluated from these measurements.To relate the relative viscoelasticity with the components of systems and their concentrations at cooling conditions the response surface methodology was used to obtain this information.The results obtained indicate that E4M promoted in general a decrease of relative viscoelasticity only in the combined systems. When E4M was in combination with HSP, two regions in the plot with the lowest tan. δ can be possible to obtain. One of them was at lower HSP and E4M concentrations and the other at the HSP and E4M highest concentrations. In similar way, when E4M was in combination with κC an increase of relative viscoelasticity was observed at the lowest E4M and κC concentrations and other region was found at the highest E4M and κC concentrations.In other hand, κC would enhance a higher relative viscoelasticity, however, when this polysaccharide was used in combination with hydrolyzed soy protein and/or E4M, a decrease of relative viscoelasticity was observed in the mixed systems.It can be concluded that E4M is the principal component which determines high viscoelastic characteristics in combination with hydrolyzed soy proteins and κC at 10 °C.